Effect of plasma nesfatin-1 level on clinical and quality of life in patients with fibromyalgia syndrome - Elbasti, Muhammet Sahin; Gulkesen, Arif; Alkan, Gokhan; Akgol, Gurkan; Kaya, Arzu; Kaman, Dilara (Lippincott Williams & Wilkins, 2025)
This study investigates the relationship between serum nesfatin-1 level and clinical parameters such as pain intensity, disease activity, anxiety, depression, sleep quality, and quality of life in patients with fibromyalgia syndrome (FMS). Eighty-two FMS cases and 82 control patients, aged between 18 to 65, were included in this cross-sectional study. The Visual Analog Scale, Fibromyalgia Impact Questionnaire, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Pittsburgh Sleep Quality Index, and Short Form-36 were used to analyze the patients. Nesfatin-1 levels were determined using an enzyme-linked immunosorbent assay. The Visual Analog Scale, BDI, BAI, Pittsburgh Sleep Quality Index, and Fibromyalgia Impact Questionnaire scores were significantly higher in patients with FMS (P < .05). The quality of life scores of the patients with FMS were significantly lower (P < .05). Serum nesfatin-1 concentration was significantly lower in patients with FMS (P < .05). A significant positive correlation (P < .05) was detected between nesfatin-1 and BAI and BDI scores in the FMS patient group, and a significant negative correlation (P < .05) was found between nesfatin-1 and body mass index. Low plasma nesfatin-1 levels may contribute to the pathological changes in FMS. Additionally, nesfatin-1 may be involved in mediating anxiety and depression-related responses in FMS patients.
Keywords: anxiety; depression; FMS; nesfatin-1; quality of life